Stabilization of Water-in-Water Emulsions by Polysaccharide-Coated Protein Particles - de Freitas, Rilton A (Langmuir : the ACS journal of surfaces and colloids, 2016)
The phase diagram of mixtures of xyloglucan (XG) and amylopectin (AMP) in aqueous solution is presented. Water-in-water emulsions prepared from mixtures in the two-phase regime were studied in detail, and the interfacial tension was determined. It is shown that the emulsions can be stabilized by addition of β-lactoglobulin microgels (βLGm), but only at pH ≤ 5.0. Excess βLGm preferentially entered the AMP phase at pH > 5.0 and the XG phase at lower pH. The inversion was caused by adsorption of XG onto βLGm that started below pH 5.5. It is shown that modification of the surface of particles by coating with polysaccharides is a potential lever to control stabilization of water-in-water emulsions